Magnetic-mediated hyperthermia for cancer treatment： Research progress and clinical trials - 赵凌云 刘嘉毅 欧阳伟炜 李丹叶 李立 李利亚 唐劲天 (Chinese physics B, 2013)
Research progress and frontiers of magnetic-mediated hyperthermia （MMH） are presented, along with clinical trials in Germany, the US, Japan, and China. Special attention is focused on MMH mediated by magnetic nanoparticles, and multifunctional magnetic devices for cancer multimodality treatment are also introduced.